2016
DOI: 10.1093/jpe/rtw032
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of germination strategy in the invasive speciesUlex europaeus

Abstract: Aims. The study of the adaptive potential of the germination patterns of invading species enables us to identify some traits linked with their capacity to colonize new sites, and to better understand their area of distribution. The aim of the present study is to determine the germination pattern of Ulex europaeus, a cosmopolitan invasive species, in relation to temperature and to explore its potential evolution in a tropical invaded region since its introduction from Europe. Methods. We studied the germination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 80 publications
1
34
0
2
Order By: Relevance
“…Kudoh et al (2007) found that Japanese (introduced) populations of Cardamine hirsuta exhibited stronger initial dormancy and more persistent seed banks than European (native) populations, both of which can increase the probability of survival in the novel range. An opposite pattern of seed dormancy was reported for introduced populations of Ulex europaeus which showed less physical dormancy, perhaps selected by decreased seed predation in the introduced range (Udo et al 2017).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Kudoh et al (2007) found that Japanese (introduced) populations of Cardamine hirsuta exhibited stronger initial dormancy and more persistent seed banks than European (native) populations, both of which can increase the probability of survival in the novel range. An opposite pattern of seed dormancy was reported for introduced populations of Ulex europaeus which showed less physical dormancy, perhaps selected by decreased seed predation in the introduced range (Udo et al 2017).…”
Section: Introductionmentioning
confidence: 82%
“…In contrast, the earliest part of the life cycle, germination, has received relatively little attention. (Udo et al 2017;Gioria and Pyšek 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Further investigation would be needed in order to control the maternal effects between these populations, by growing plants from seeds for two generations under the same environmental conditions ( Fenster and Galloway, 2000 ). Future research comparing germination dynamics of seeds of the two water primroses from their native range, tested in native and exotic range conditions, could yield valuable information about the evolution of germination capacity ( Hierro et al, 2009 ; Gioria and Pyšek, 2017 ; Udo et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of time ( t g , days) taken for cumulative germination to reach different percentiles (g) for successive increments of 5% germination were interpolated from the germination progress curves ( Covell et al., 1986 ). Germination rate (1/ t 25 ) was plotted as a function of temperature and regressed using a linear model ( Udo et al., 2017 ), to estimate the base temperature ( T b ) below which germination rate was equal to zero. The slope of the linear regression line corresponded to the reciprocal of the thermal-time requirement at suboptimal temperatures ( θ 25 ).…”
Section: Methodsmentioning
confidence: 99%